Feminism Analysis of Forms of Domestic Violence Against Women in the Novel Heartbreak Motel By Ika Natassa - Furqon, Hendrik; Santi, Alfika Tri Maya (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
Women are one of the literary objects that are always interesting to discuss. In this modern era, many women in real life experience oppression from men, so women are seen as weak by men because their lives depend on men. The focus of this research is violence against women in the household (domestic violence). Against this background, this study aims, namely (1) forms of physical violence against women; (2) forms of emotional violence against women; (3) the impact of physical violence and emotional violence on women. Method used in this study is the theory of feminism with qualitative descriptive research methods. The results of this study indicate that there are 6 analytical data on physical violence against women in Ika Natassa's novel Heartbreak Motel, 9 analytical data on emotional violence against women in Ika Natassa's novel Heartbreak Motel, and 13 analytical data on the impact of physical violence and emotional violence on women. in the novel Heartbreak Motel by Ika Natassa.